Ultrasonography of the Adult Thoracic and Lumbar Spine for Central Neuraxial Blockade - Ki Jinn Chin; Manoj K. Karmakar; Philip Peng; David S. Warner (2011)
The role of ultrasound in central neuraxial blockade has been underappreciated, partly because of the relative efficacy of the landmark-guided technique and partly because of the perceived difficulty in imaging through the narrow acoustic windows produced by the bony framework of the spine. However, this also is the basis for the utility of ultrasound: an interlaminar window that permits passage of sound waves into the vertebral canal also will permit passage of a needle. In addition, ultrasound aids in identification of intervertebral levels, estimation of the depth to epidural and intrathecal spaces, and location of important landmarks, including the midline and interlaminar spaces. This can facilitate neuraxial blockade, particularly in patients with difficult surface anatomic landmarks. In this review article, the authors summarize the current literature, describe the key ultrasonographic views, and propose a systematic approach to ultrasound imaging for the performance of spinal and epidural anesthesia in the adult patient.